Vegetation development on the glacier moraines in Oobloyah Valley, Ellesmere Island high arctic Canada - Okitsu, Susumu; Sawaguchi, Shin-ichi; Hasegawa, Hirohiko; Kanda, Hiroshi (National Institute of Polar Research, 2004)
P(論文) The process of the vegetation development on glacier moraines was surveyed in the lower stream area of Oobloyah Valley (80°50'N, 82°45'W), Ellesmere Island, high arctic Canada. Four glacier moraines, and an outwash plane with different establishment periods in the proglacial field of Arklio Glacier, were surveyed .The oldest moraine was estimated to have been established during the Full Glacial, ca. 25000-35000 years ago, and the youngest one during the Little Ice Age, ca. 250 years ago. The vegetation properties such as number of species per study plot, cover of vegetation, lichens and bryophytes showed constant increase the moraine age, suggesting directional vegetation development. Changes in the species composition were such that new species successively appeared during the establishment of the moraines without obvious replacement of the species. It was concluded that the manner of the vegetation development was directional-nonreplacement succession even under extreme high arctic environment, differing from the generally accepted view that under an extreme high arctic environment nondirectional-nonreplacement succession prevails. Vegetation physiognomy approached Cassiope tetragona-dominated dwarf shrub heath, which generally prevails in more southern regions than Ellesmere Island. The period required for the vegetation development in the study area was assumed to be quite long, probably at least ca. 20000 years. departmental bulletin paper